2013
DOI: 10.1007/s11033-013-2693-1
|View full text |Cite
|
Sign up to set email alerts
|

Lack of association of Lysyl oxidase (LOX) gene polymorphisms with intracranial aneurysm in a south Indian population

Abstract: Intracranial aneurysm (IA) accounts for 85 % of haemorrhagic stroke and is mainly caused due to weakening of arterial wall. Lysyl oxidase (LOX) is a cuproenzyme involved in cross linking structural proteins collagen and elastin, thus providing structural stability to artery. Using a case-control study design, we tested the hypothesis whether the variants in LOX gene flanking the two LD block, can increase risk of aSAH among South Indian patients, either independently, or by interacting with other risk factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Reduced extracellular matrix is a prominent feature of cerebral aneurysms. In an earlier study we reported that lysyl oxidase (LOX) is an enzyme which is involved in covalent cross linking of these fibrous proteins by the formation of aldehydes between lysine residues that insolubilize these extracellular proteins namely collagen and elastin ( Kagan and Li, 2003 ), thus giving strength to intracranial arteries was not found to be associated with IA in our study population ( Sathyan et al, 2013 ). Proteoglycan Versican ( VCAN ) is a putative candidate gene for IAs as it plays an important role in extracellular matrix assembly and is localized near a previously implicated locus for IAs on chromosome 5q22–31 ( Onda et al, 2001 ).…”
Section: Introductionmentioning
confidence: 63%
“…Reduced extracellular matrix is a prominent feature of cerebral aneurysms. In an earlier study we reported that lysyl oxidase (LOX) is an enzyme which is involved in covalent cross linking of these fibrous proteins by the formation of aldehydes between lysine residues that insolubilize these extracellular proteins namely collagen and elastin ( Kagan and Li, 2003 ), thus giving strength to intracranial arteries was not found to be associated with IA in our study population ( Sathyan et al, 2013 ). Proteoglycan Versican ( VCAN ) is a putative candidate gene for IAs as it plays an important role in extracellular matrix assembly and is localized near a previously implicated locus for IAs on chromosome 5q22–31 ( Onda et al, 2001 ).…”
Section: Introductionmentioning
confidence: 63%
“…They reported that serpine 1 ( SERPINE 1, combined OR 1.27, p =0.004), FBN2 (combined OR 1.37, p =0.01), and alpha 1 type IV collagen ( COL4A1 , combined OR 1.22, p =0.007) were related to IA; however, no association of SNPs between the LOX gene and IA was demonstrated. Sathyan, et al 7 did not find allelic or genotypic variants of the LOX gene in a South Indian population with IA. Several genome-wide association studies 26 27 also did not demonstrate the 5q22-31 loci for IA formation.…”
Section: Discussionmentioning
confidence: 89%
“…In addition, no significant associations of LOX variants with IA were observed in a South Indian population. 7 Nevertheless, LOX has been reported to be a risk factor for coronary artery disease (CAD) and cerebral stroke. Ma, et al 8 found that G473A polymorphism of LOX was associated with CAD.…”
Section: Introductionmentioning
confidence: 99%
“…also found that the C allele of LOX rs3900446 and the G allele of rs763497 with increased risk of IA (OR, 20.15; P = 4.8 × 10 -5 and OR, 2.26; P = 4.8 × 10 -5 ) in Korean population, respectively ( 25 ). However, the polymorphisms of LOX gene is not associated with IA in Japanese and Dutch ( 23 ), central European ( 22 ) and South Indian ( 24 ) populations. Lan Ma et al.…”
Section: Discussionmentioning
confidence: 99%
“…So far, few population studies have explored associations between polymorphisms in LOX family genes and IA, and the results were inconsistent. For instance, associations between LOX gene polymorphisms and IA have not been found in Japanese, Central European, and South Indian populations ( 22 24 ). However, a recent population study in Korea found three SNPs of LOX (rs2303656, rs3900446, and rs763497) were significantly associated with IA (maximum OR, 20.15; P = 4.8 × 10 –5 ) ( 25 ).…”
Section: Introductionmentioning
confidence: 99%